A review on climate change and Malaysia’s actions - Narinderjeet Kaur; Syed Sharizman Syed Abdul Rahim; Zahir Izuan Azhar; Mohd Yusof Ibrahim; Mohammad Saffree Jeffree; Mohd Rohaizat Hassan (2019)
One of the biggest global health threats of the 21st century is climate change It is so catastrophic that the climate action has been given a platform as it is the 13th goal of the 17 United Nations Sustainable developmental goals (SDG). This review seeks to understand the factors causing climate change, followed by understanding the impact it has on individual and population health. We also identify the strategies to control and prevent further climate change. Methods: Reviews of local and international articles from the past ten years was conducted. The focus of the review was the causes health effects as well as strategies. Data base used was Pro Quest. Results: This review identified that the main contributor to climate change are man-made activities such as fossil fuels combustion, livestock farming, and deforestation. This change in climate has many repercussions from mass migrations, increase communicable diseases as well as an increase in extreme weather events and natural disasters. All this eventually leads to the deterioration of individual and population health. Strengthening adaptivity to climate-related hazard, climate change integration into national policies, education, awareness-raising, impact reduction and early warning are actions that are present in Malaysia to manage this crisis. Conclusion: Climate change is occurring globally, and its presence can no longer be denied. Actions have been put forth, but only when its importance and impact is taken seriously will the positive changes be sustainable.